2006
DOI: 10.1007/s10151-006-0276-z
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based treatment algorithm for anal fissure

Abstract: Guidelines for the treatment of anal fissure have been published in the USA and UK but differ. Many centers follow guidelines based on local experience. In December 2005, we met with the aim of developing an evidence-based treatment algorithm for anal fissure, applicable to both primary and secondary care. This algorithm may rationalize the treatment of anal fissure in primary and secondary care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 21 publications
0
13
0
6
Order By: Relevance
“…At least two recent guidelines by the American Society of Colon and Rectal Surgeons and the European Society of Coloproctology defined LIS as the surgical treatment of choice for refractory anal fissures [12,13]. Although LIS has a cure rate of over 95%, recent studies have reported the risk of incontinence of feces or flatus after this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…At least two recent guidelines by the American Society of Colon and Rectal Surgeons and the European Society of Coloproctology defined LIS as the surgical treatment of choice for refractory anal fissures [12,13]. Although LIS has a cure rate of over 95%, recent studies have reported the risk of incontinence of feces or flatus after this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based algorithms for the treatment of anal fissures were developed in 2006 by clinicians from across Europe [184]. The algorithms are for the treatment of fissures in both primary and secondary care (Fig.…”
Section: Current Guidelinesmentioning
confidence: 99%
“…However, those patients suffering persistent but asymptomatic fis- Fig. 2a, b Algorithm for the treatment of anal fissure (taken from [184]). a Initial presentation (primary care).…”
Section: Current Guidelinesmentioning
confidence: 99%
“…But, for the majority of patients, this treatment makes it possible to avoid irreversible resection of the internal anal sphincter and the postoperative consequences. Since the introduction of topical nitrates, the number of surgical interventions performed for anal fissure has fallen by 72% in England and 61% in Scotland [4].…”
Section: Dear Sirmentioning
confidence: 99%